Non-exhaust PM2.5 from Road Dust Resuspension in Tirana Street Canyons: An AP-42 Empirical Approach and Meteorological Influences - Premti, Dhurata; Manaj, Hasime; Prifti, Terkida; Kurti, Lotar; Pinguli, Luljeta; Ylli, Fatos; Malollari, Ilirjan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Central Tirana is characterized by high population density and severe traffic congestion, conditions that strongly enhance road dust resuspension as a significant non-exhaust source of fine particulate matter. This case study investigates the main features of the phenomenon, with particular attention to the street canyon effect caused by building height and the vertical gradients of pollutant concentration, an aspect that remains largely unexplored in the Albanian urban setting.
Keywords: road dust resuspension; non-exhaust emissions; street canyon effect; urban traffic; PM2.5